Framework of Network Security and Cryptography: An Impact Analysis: Exploring Principles and Systems of Cryptography in Network Security (Journal of Advances and Scholarly Researches in Allied Education, 2017)
Computer networks that are involved in regular transactions and communication within the society, government, individuals, or business require security. The most common and simple way of protecting a network resource is by assigning it a unique name and a corresponding password. Cryptography historically dealt with the construction and analysis of protocols that would prevent any third parties from reading a private communication between two parties. In the digital age, cryptography has evolved to address the encryption and decryption of private communications through the internet and computer systems, a branch of cyber and network security, in a manner far more complex than anything the world of cryptography had seen before the arrival of computers. Secure Communication refers to the scenario where the message or data shared between two parties can’t be accessed by an adversary. In Cryptography, an Adversary is a malicious entity, which aims to retrieve precious information or data thereby undermining the principles of information security. Data Confidentiality, Data Integrity, Authentication and Non-repudiation are core principles of modern-day cryptography. In this paper cryptography along with its principles and cryptographic systems with ciphers are studied.